(untitled) (Ann Arbor, Mich, 1988)
Contents: Ethnic groups and the control of natural resources in Kelantan, Malaysia; ethnic concentrations; changing ethnicity and social resources in a Thai-Mon village.
Keywords: Ethnology,Human ecology,Dân tộc học,Sinh thái con người; Southeast Asia,Southeast Asia,Đông Nam Á,Đông Nam Á